Service and performance adjusted life cycle assessment: a methodology for dynamic assessment of environmental impacts in infrastructure systems. Issue 3 (3rd July 2017) - Batouli, Mostafa; Mostafavi, Ali
Abstract: Infrastructure systems are at the core of the sustainability challenge. Currently life cycle assessment (LCA) is widely used for assessing environmental sustainability of infrastructure systems. However, infrastructure systems have specific traits that are incompatible with the requirements of LCA. In particular, infrastructure systems do not have definite 'life cycle' as a basis of LCA. In addition, environmental performance of infrastructure systems depends on the dynamic changes in the level of service and performance of infrastructure normally not captured in existing LCA approaches. The objective of the research presented in this paper attempts to address the limitations of existing LCA approaches by creating a service and performance adjusted LCA (SPA-LCA) methodology, one which is specifically tailored for the requirements of environmental assessment of infrastructure systems. Among other improvements, the created methodology introduces a dynamic conception of life cycle inventory analysis and a service-based environmental accounting for the impact assessment phase of LCA. A simulation-based computational model is created to enable implementation of the SPA-LCA methodology. The SPA-LCA method and the created computational model are tested in a case study related to assessing the environmental impacts of a pavement network. Results include assessing impacts of different budget and demand scenarios on the environmental performance of the case study network. The results indicate capabilities of SPA-LCA methodology in addressing the limitations of existing LCA approaches for assessing environmental impacts of infrastructure systems.